Surface roughness of nanofilled and nanohybrid composite resins exposed to kretek cigarette smoke - Laksmiari Setyowati; S. Setyabudi; Johanna Chandra (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Cigarette smoking is a public health issue that may influence the physical properties of dental composites. Surface roughness is one of the physical properties of restorative materials potentially influencing their success. The use of nanofilled and nanohybrid composites in dentistry has increased substantially over the past few years. Purpose: The purpose of this study was to evaluate the surface roughness of nanofilled and nanohybrid composite resins exposed to kretek cigarette smoke. Methods: Twelve cylindrical specimens of each material were prepared and divided into two groups (n=6). In the control groups, the specimens were immersed in distilled water for 24 hours at 37°C, with the water being renewed daily. For the experimental groups, the specimens were exposed to kretek cigarette smoke on a daily basis, then washed and soaked in distilled water at 37°C. After 21 days, the specimens were measured using a Surface Roughness Tester and the data was then statistically analyzed. Results: An Independent-T Test revealed that there were statistically significant differences in the surface roughness between the control and experimental groups of both nanofilled and nanohybrid composites, as well as between the nanofilled experimental group and the nanohybrid experimental group. Conclusion: Exposure to kretek cigarette smoke can increase the surface roughness of nanohybrid composites to a significantly greater extent than nanofilled composites.